2019
DOI: 10.1111/os.12428
|View full text |Cite
|
Sign up to set email alerts
|

Robot‐assisted Percutaneous Transfacet Screw Fixation Supplementing Oblique Lateral Interbody Fusion Procedure: Accuracy and Safety Evaluation of This Novel Minimally Invasive Technique

Abstract: Objectives Percutaneous transfacet screw fixation (pTSF) is a minimally invasive posterior fixation technique supplementing oblique lateral interbody fusion (OLIF) for lumbar spinal disorders. Accurate screw insertion is difficult to achieve and technically demanding under 2‐D fluoroscopy. Recently developed robot‐assisted spinal surgery demonstrated a high level of accuracy of pedicle screw insertion and a low complication rate. No published study has reported this combination technique. The aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 29 publications
2
31
0
1
Order By: Relevance
“…In a recent comparable experimental prospective study, Wu et al studied the safety and accuracy of robot‐assisted percutaneous transfacet screw fixation combined with oblique lateral interbody fusion. According to these results, 95.8% of screws had a cortex perforation < 2 mm and 4.2% had a cortex perforation of >2 mm, which is comparable to our study at 98.2% and 1.8%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent comparable experimental prospective study, Wu et al studied the safety and accuracy of robot‐assisted percutaneous transfacet screw fixation combined with oblique lateral interbody fusion. According to these results, 95.8% of screws had a cortex perforation < 2 mm and 4.2% had a cortex perforation of >2 mm, which is comparable to our study at 98.2% and 1.8%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The TiRobot system is the first orthopaedic surgical robot researched and developed in China, with completely independent intellectual property. It can be used in spinal surgery and traumatic orthopaedic surgery. This robotic technique is a practical clinical application of computer‐assisted minimally invasive spine surgery (CAMISS), which achieves better clinical outcomes with the advantages of less invasion, less injury, and better recovery, and has also became the gold standard for spine surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The comprehensive security protection mechanism can ensure the safe operation of the robot with strong practicability, a high degree of freedom, and good repeatability. Previous studies have reported that it can also significantly reduce intraoperative radiation exposure [ 23 ]. In addition, it can help young spinal surgeons rapidly improve their surgical techniques while shortening their learning curve [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Safety is the premise of the application and promotion of robotic surgery; nevertheless, clinicians often stop using robotic surgery because they are worried about its intraoperative safety. The Tinavi robot does not enter a patient’s body, it assists the doctor in completing an accurate operation, and it has multiple safety strategies, including a safety activity control area, safety control strategy, and emergency operation brake light [ 25 , 26 ], which can fully meet surgical safety requirements.…”
Section: Discussionmentioning
confidence: 99%